A Comparative Study between Laser Beam Ceilometer and Algorithm for Continuous Evaluation of Cloud Base Height, Temperature, and Cloud Coverage in Logan City, USA - Esmaiel Malek (Current Approaches in Science and Technology Research Vol. 3, 2021)
This article addresses the application of pyrgeometers, pyranometers and some basic weather parameters to evaluate cloud base height, cloud base temperature, and cloud coverage at local scale throughout the year. The ground-based laser beam ceilometers are used at the Automated Surface Observing Systems (ASOS) in major airports in the U.S. to measure the cloud base height and report the sky conditions on an hourly basis or at shorter intervals. These laser ceilometers are fixed-type whose transmitters and receivers point straight up at the cloud (if any) base. They are unable to detect clouds that are not above the sensor. To report cloudiness at the local scale, many of these types of ceilometers are needed. A single cloud hanging over the sensor will cause overcast readings, whereas, a hole in the clouds above the sensor could cause a clear reading to be reported. To overcome this problem, we have set up a ventilated radiation station at Logan - Cache airport, Utah, U.S .A., since 1995. This airport is equipped with one of the above-mentioned ceilometers. This radiation station (composed of pyranometers, pyrgeometers with fields of view of 150o), and net radiometer provide continuous measurements of incoming and outgoing shortwave and longwave radiation and net radiation throughout the year. Considering the additional longwave radiation captured by the facing-up pyrgeometer during cloudy skies, coming from the cloud in the wave band (8-13 ?m) which the gaseous emission lacks, we developed an algorithm which provides the continuous cloud information (cloud base height, cloud base temperature, and percent of skies covered by cloud) at local scale during the day and night throughout the year. Comparisons between the ASOS and the model data during the period June, 2004, are reported in this article. The proposed algorithm is a promising approach for evaluation of the cloud base temperature and height, and percent of skies covered by cloud and its effects on aviation throughout the year. Having enough pyrgeometers and the necessary surface weather parameters, the study can be expanded to regional scale for continuous evaluation of clouds.